A STUDY ON UNDERSTANDING WORKPLACE SEXUAL HARASSMENT AND ITS ATTRIBUTES - Vishal Sridhar, Tejaswini Sivaprakasam, Gopinathan N (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
"Uninvited and unwelcome verbal or physical behaviour of a sexual nature especially by a person in authority toward a subordinate (such as an employee or student)". Merriam Sexual harassment is unwanted sexual action which would make a person feel offended, intimidated. Sexual harassment said to be non-consensual interaction. It is a behaviour that is not mutually agreed upon. Sexual harassment can be committed against men and women. Sexual harassment is against the law and is covered under the Equal Opportunity Act, 2010. Sexual harassment at the workplace does not only include employers and employees but also volunteers and unpaid workers. Sexual harassment need not necessarily be of sexual in nature; it can also be offensive remarks about a person’s sex. There has to be enough emphasis on the sensitization of sexual harassment at the workplace. In India, Article 21 of the Constitution ensures the "Right to life and personal liberty" of an individual, therefore when a person is victimized to sexual harassment his/her fundamental right is being violated. This paper tries to bring out various aspects of workplace sexual harassment.